Acquired long QT syndrome in hospitalized patients - Yu, Haixu; Zhang, Li; Liu, Jinqiu; Liu, Ying; Kowey, Peter R.; Zhang, Yanli; Chen, Yue; Wei, Yushan; Gao, Lianjun; Li, Huihua; Du, Jie; Xia, Yunlong (Heart rhythm, 2017)
Acquired long QT syndrome (ALQTS) has long been overlooked in clinical practice. Recent studies reported that severe ALQTS (QTc ≥500 ms) in hospitalized patients is associated with increased all-cause mortality. The purpose of this study was to determine the role of ALQTS in the clinical outcomes of hospitalized patients. Electronic medical records were reviewed to identify severe ALQTS in hospitalized patients in a single study center from September 1, 2013, to February 28, 2014. Up to 1-year follow-up was conducted in the ALQTS subjects and compared with age-, gender-, and admitting diagnosis-matched hospitalized patients with a normal QT interval. Severe ALQTS (QTc 529 ± 38 ms) was seen in 0.7% (293/41,649) of hospitalized patients, of whom 86% were treated in noncardiology departments. All-cause mortality was 32% in the ALQTS group vs 14% in the control group (P <.001) during follow-up of 255 ± 63 days. Syncope and life-threatening ventricular arrhythmia were more frequent in patients with severe ALQTS (6% vs 0.6%, P <.0001). Cerebral hemorrhage (odds ratio [OR] 6.405, 95% confidence interval [CI] 2.341–17.525), cancer (OR 5.937, 95% CI 2.658–13.260), infection (OR 2.207, 95% CI 1.124–4.333), and end-stage disease (OR 2.092, 95% CI 1.045–4.191) are the major contributors to all-cause mortality in ALQTS. Severe ALQTS is not uncommon in hospitalized patients. It can be easily overlooked because the majority of patients with severe ALQTS are treated in noncardiology departments. The clinical outcome of severe ALQTS is poor. Removing QT-prolonging factors may reduce the risks of fatal arrhythmia and sudden death in patients with ALQTS.